Borboletas frugívoras (Lepidoptera: Nymphalidae) em florestas de Mata Atlântica do Parque Nacional do Iguaçu, Paraná, Brasil - Graciotim, Camila (2014)
Faunal studies, used as the main building blocks for conservation practices, have potential importance in minimizing environmental impacts. From this, this study sought to analyze the community of fruit-feeding butterflies of the Semideciduous Forest and Araucaria Forest of Iguassu National Park, promoting the comparison of composition, richness, abundance, dominance and similarity of the assemblages as their association with environmental descriptors evaluated in each phytophysiognomy. Field work was carried out monthly between November 2012 and May 2013, using Van Someren-Rydon traps with bait consisting of mashed banana in fermented sugarcane juice. In each phytophysiognomy, we used 15 traps in pre-defined transects that were revised each 24 h during five days per sampling occasion. At the end of six samplings and 900 traps/day as total effort, 1,127 individuals representing 69 species and four subfamilies of fruit-feeding butterflies were recorded. The sampled richness was lower than the Jacknife 1 and Bootstrap estimated values, indicating the importance of increasing the sampling effort. Satyrinae was the subfamily with greater richness and abundance in both areas. Among the total species registered, 11 were new records for the Iguassu National Park. Ordination analysis showed a low segregation of assemblages composition and a difference of 27.2 % between them. The influence of environmental descriptors showed that the set of variables: light, canopy cover and number of trees were the most important in structuring the assemblages of frugivorous butterflies sampled. The obtained results shall provide subsidies for a better knowledge of the diversity of the Atlantic Forest butterflies, contributing to the Management Plan of the Iguassu National Park.